Caroço de pêssego triturado: alternativa de substrato para produção de mudas - Mieth, Patrícia (2016)
With the increase of the demand for forest seedlings, both training for business stands and recovery of degraded areas, there is a growing concern with the reduction of costs and the need to follow sustainability standards in the production of seedlings. For this reason, renewable materials have been studied and used for formulation of substrates, and the lump of peach has potential to be used with this purpose, which has the physical structure rigid that do not decomposes with ease and, when triturated, retains particles of various granulometries. The present study had as objectives: I - Evaluate the characteristics peach lump triturated for use as a component of the substrate for plants; II - to investigate the influence of substrates with different proportions of peach lump triturated seedling growth of E. dunnii seeds in the nursery and the performance in the field. Were used different proportions of mixture [100:0%, 80:20%; 60:40%; 40:60%; 20:80%; 0:100% (volume:volume)] from peach lump triturated (C) and commercial substrate (S), composing the group 1 (CxS), and C and peat brown (T), called the group 2 (CxT). It was evaluated the physical, chemical and the content of the macronutrients of mixtures. In the nursery evaluations were made of height (H), collar diameter (DC), H/DC, dry mass carrier, root dry mass, total dry mass, the quality index of Dickson, leaf area, root length and volume, ease of withdrawal of the seedlings in the polyethylene tube, aggregation of roots and photochemical efficiency of photosystem II maximum In the field, it was evaluated the survival, the increment in the growth in height and diameter of the stem base diameters and physiological variables during 240 days. In general, the results obtained allow us to infer that the peach lump triturated presents physical and chemical characteristics suitable for use as a component of substrates, increasing the density wet and dry, the material consisting of aeration and pH, while the total porosity, water holding capacity and the electric conductivity had lower values for the substrates with or with a higher proportion of peach lump triturated. In the production of seedlings of E. dunnii seeds, this material reduced the growth of the same, but can be used as a component of substrate in all the proportions of the mixture with commercial substrate without interfering with their development in the field, but with proportions greater than 20% change has difficulty be removed from the cartridge and less aggregation, reducing the yield of the operations in the field. Mixed with brown peat, it is recommended to use proportions between 15% and 30% of crushed peach kernel allowing better growth of seedlings in the nursery and good performance after planting.